Magnetic resonance imaging features of bile duct adenoma - Huang, Mengyue; Huang, Mengna; Gao, Xuemei; Zhang, Yong; Cheng, Jingliang; Zhu, Jinxia; Li, Caixia; Liu, Jingjing (Frontiers in Oncology, 2023)
Objectives: To evaluate the magnetic resonance imaging (MRI) features of bile duct adenoma. Methods: The data of 28 patients [with 32 pathologically confirmed bile duct adenomas, including 15 with malignant change (malignant group) and 17 without malignant change (benign adenoma group)] were retrospectively reviewed. Abdominal MRI was performed for all patients; in addition, dynamic enhanced MRI was performed for 18 lesions. The MRI features, including lesion location, maximum size, morphology, signal characteristics, enhancement type, and appearance of the bile duct, were assessed by two abdominal radiologists. Apparent diffusion coefficient (ADC) values were measured and compared. Results: Of the 32 bile duct adenomas, 22 (68.75%) involved the common bile duct (CBD). While 14/32 (43.75%) lesions presented as focal eccentric type masses, 9/32 (28.13%) presented as plaque-like masses, 4/32 (12.50%) as bile duct casting masses, and 5/32 (15.62%) as infiltrative masses. A frond-like superficial appearance was seen in 8/32 (25%) lesions. Infiltrative masses were significantly more common in the malignant group than in the benign adenoma group (P = 0.015). While 23/32 (71.88%) lesions were isointense on T1-weighted imaging (T1WI), 24/32 (75%) were hyperintense on T2-weighted imaging (T2WI). Bile duct dilatation was present upstream of the lesion in all cases. Bile duct dilatation at the lesion was seen in 24/32 (75%) cases and downstream of the lesion in 6/32 (18.75%) cases. Of the 18 lesions that underwent dynamic enhanced MRI, 14 (77.78%) showed moderate enhancement, and 13 (72.22%) showed persistent enhancement. On diffusion weighted imaging (DWI), 27/32 (84.37%) lesions showed hyperintensity. Mean ADC value was comparable between the malignant group and the benign adenoma group (P = 0.156). Conclusions: Bile duct adenoma primarily presents as intraductal growth in the common bile duct, usually with bile duct dilatation at the lesion site or upstream to it. Most lesions are isointense on T1WI, hyperintense on T2WI and DWI, and show moderate enhancement. A superficial frond-like appearance of the lesion, and bile duct dilatation at the lesion or downstream to it, might be characteristics of bile duct adenoma. An infiltrative appearance might indicate malignant transformation.